2011
DOI: 10.1017/s1755048311000149
|View full text |Cite
|
Sign up to set email alerts
|

Not in His Image: The Moderating Effect of Gender on Religious Appeals

Abstract: Religious appeals have been part and parcel of campaign strategy for decades. Most often, however, these appeals to have come from men, but little is known about howwomenwould fare using religious appeals on the campaign trail. To remedy this, we used an experimental design to examine voter reaction to religious appeals from a female and a male candidate competing for an open United States Senate seat. We find that women's use of religious appeals is governed by the dynamics of tokenism — reinforcing tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Scholars have also shown that the concentration of politically-active, conservative evangelicals in states inversely relates to the proportion of women in state legislatures, suggesting support for traditional gender roles translates into preferences for male candidates and leadership (Merolla, Schroedel, and Holman 2007). Future research could explore the effect of masculine views of authority on gender stereotypes, support for female candidates, and women's willingness to run for political office (Calfano and Djupe 2011). Given that we find different effects for men and women, continued research on how these beliefs shape political behavior and engagement among women is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have also shown that the concentration of politically-active, conservative evangelicals in states inversely relates to the proportion of women in state legislatures, suggesting support for traditional gender roles translates into preferences for male candidates and leadership (Merolla, Schroedel, and Holman 2007). Future research could explore the effect of masculine views of authority on gender stereotypes, support for female candidates, and women's willingness to run for political office (Calfano and Djupe 2011). Given that we find different effects for men and women, continued research on how these beliefs shape political behavior and engagement among women is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Calfano and Djupe (2011) demonstrate how covert religious cues stop being advantageous when females deliver them because citizens tend to more critically evaluate messages from females. Calfano and Djupe (2011) demonstrate how covert religious cues stop being advantageous when females deliver them because citizens tend to more critically evaluate messages from females.…”
Section: Future Researchmentioning
confidence: 93%
“…Politicians can use subtly coded religious language and Americans pick up on it, altering their assessments of candidates for elected office (Calfano and Djupe 2011). Politicians can use subtly coded religious language and Americans pick up on it, altering their assessments of candidates for elected office (Calfano and Djupe 2011).…”
Section: Prototypicality Religion and National Identitymentioning
confidence: 99%